Migration patterns and putative spawning habitats of Atlantic halibut (Hippoglossus hippoglossus) in the Gulf of St. Lawrence revealed by geolocation of pop-up satellite archival tags. (22nd June 2017) - Le Bris, Arnault; Fisher, Jonathan A D; Murphy, Hannah M; Galbraith, Peter S; Castonguay, Martin; Loher, Timothy; Robert, Dominique
Abstract: Characterizing migratory behaviours contributes to the sustainable management of marine fishes by resolving stock structure and identifying the timing and locations of events within fish life cycles. The migratory behaviour of Atlantic halibut ( Hippoglossus hippoglossus ) in the Gulf of St. Lawrence (GSL), Canada was characterized over an annual cycle using pop-up satellite archival tags ( n = 15). Daily probability density functions of individual halibut positions were estimated using a geolocation model specifically developed to track demersal fish species in the GSL. Reconstructed migration routes ( n = 8) revealed that Atlantic halibut displayed seasonal migrations, moving from deeper offshore waters in the winter to shallower nearshore waters in the summer. Variability in migratory behaviours was observed among individuals tagged at the same location and time. One individual resided year round in the vicinity of the tagging site, three individuals displayed homing behaviour, and four individuals did not return to the tagging site. The identification of presumed spawning rises for two individuals suggested that spawning of Atlantic halibut occurred in the GSL. Although based on a limited number of individuals, these results suggest that Atlantic halibut in the GSL forms a philopatric population, supporting the current separate management of this stock from the adjacent Scotian Shelf and southern Grand Banks stock.